Mana Māori. The Power of New Zealand's First Inhabitants - Wonu Veys, Fanny (Leiden University Press, 2010)
This book takes you on a journey exploring the histories of the country's first Polynesian discoverers, its encounters with Europeans and the subsequent settling by Westerners. Particular attention will be paid to the Dutch explorer Abel Tasman and the Dutch immigration wave of the 1950s. Through a discussion of the meeting house and meeting grounds, the relationships Maori maintain to the land will be considered. The vital role of the Treaty of Waitangi (1840) and its present-day repercussions will be looked at. Finally the role of taonga or cultural treasures embodying the ancestral identity of a Maori kin group in relation to particular lands and resources will be explained.